An investigation into the contribution of the informal sector to the improvement of livelihoods: a case study of Lupane business centre - Luphahla, Patience (Midlands State University, 2017)
This study investigated the contribution of the informal sector to the improvement of livelihoods at Lupane Business Centre. The study’s objectives were to find out the different ways in which the informal sector contributed to improvement of livelihoods in improvement of livelihoods in the Lupane community, to identify the challenges encountered by the informal traders which deters them from effectively contributing to improvement of livelihoods and identifying strategies of ensuring that the informal sector becomes a major player in community development. The study was qualitative in nature. Interviews were used to get the data needed. The study was analysed qualitatively with the researcher personally interacting with the participants. The study found that the informal sector contributed to improvement of livelihoods by enabling the informal traders to ensure household food security, take their dependents to school, buy residential property, pay for health services and clothe their dependants. The study also revealed that, lack of formal training, lack of registration, inadequate business skills, lack of access to finance and lack of support were the major challenges faced by the informal sector that minimized its contribution to community development